Upaya Peningkatan Prestasi Belajar Mata Pelajaran PKN Melalui Model Pembelajaran Make A Match Pada Materi Norma Masyarakat - Ustadzah Ustadzah (Jurnal Syntax Transformation, 2021)
The scope of the discussion in this study was treated in class VII D of SMP Negeri 17 Surakarta. With a focus on the problem "Efforts to Improve Learning Achievement in Civics Subjects through the Make a Match Learning Model in Class IV Community Norms Materials at MI Ma'arif Pulutan Sidorejo". The goal to be achieved in this research is to improve student learning outcomes in Civics subjects. This research uses classroom action research (CAR). In CAR, the research phase consists of four stages, namely planning, implementing actions, observing and reflecting. The results showed that the application of the make a match type of cooperative learning model could improve Civics learning outcomes. This is indicated by the average initial test results of 65, in the first cycle it was 81.86 and in the second cycle it rose to 91.30. The level of mastery learning also increased from the initial test, namely 25.96%, in the first cycle to 66.66% and in the second cycle it increased again to 93.33%. The conclusion of this study is that the application of the make a match type of cooperative learning model can improve PKN learning outcomes for fourth grade students of MI Ma'arif Pulutan Sidorejo